Modified cenospheres as non-sacrificial pore-forming agent for development of porous mullite ceramics entirely from industrial wastes - Choo, Thye Foo (2021)
Mullite is a widely used ceramic because it exhibits some advantageous properties such as thermal shock resistance, chemical resistance, creep resistance, high hot strength and low coefficient of thermal expansion. Driven by the need for low-cost and environmentally friendly alternatives, extensive research on the utilization of low-cost materials to produce mullite ceramics is crucial. In this study, mullite ceramics were produced entirely from aluminum dross (AD) and coal fly ash (CFA) industrial wastes. Both wastes were mixed together in different weight ratio, subsequently compacted and sintered. The effects of the sintering temperature, acid leaching and Al2O3/SiO2 ratio on the chemical, physical, thermal expansion properties of the samples were characterized in detail. The results showed that appropriate mixing ratio and acid leaching had positive effects on the mineralogy, crystallinity, and macromorphology of sintered samples. At sintering temperature of 1500 °C, high mullite content ceramics with good crystallinity were produced. The resultant ceramics exhibited excellent thermal expansion properties with coefficient of thermal expansion (CTE) values ranging from 4.0 to 5.9 ×10−6 °C−1. Modified cenospheres were used as non-sacrificial pore-forming agent to produce porous mullite ceramics. The results showed that addition of modified cenospheres leads to the increment of both total porosity and closed porosity, with the reduction of open porosity. Addition of 40 wt% of modified cenospheres to the mullite precursor, the resultant porous mullite ceramic has a total porosity of 50.2%, thermal conductivity of 1.28 Wm-1K-1, linear shrinkage of 4%, and biaxial flexural strength of 45.9 MPa. The mullite precursor was also used to produce high-temperature porous mullite washcoat. Results showed that the precursor transformed to a hierarchical porous microstructure assembled by large interlocked acicular mullite crystals. The specific surface area of the washcoat was 4.85 m2g-1, which comparable to the other high-temperature washcoats. This study offers the potential of using these industrial wastes as a sustainable alternative raw material in the development of mullite ceramics.